2010
DOI: 10.1111/j.1540-8167.2010.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy for the Prevention of Atrial Fibrillation Trial (SToP AF trial)

Abstract: Background Inflammation and oxidative stress are associated with atrial fibrillation (AF). Statins have antioxidant and anti-inflammatory properties. We tested if atorvastatin reduced AF recurrence after DC cardioversion (CV) by modifying systemic oxidative stress and inflammation. (NCT00252967) Methods and Results In a randomized, double-blinded, placebo-controlled trial, patients with atrial fibrillation/flutter (AF) were randomized to receive either atorvastatin 80 mg (n=33) or placebo (n=31) before CV. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 43 publications
3
57
0
Order By: Relevance
“…100 In the statin therapy for the prevention of atrial fibrillation trial, 64 patients were randomized to atorvastatin or placebo starting 1 week before cardioversion, then continued for 12 months. 101 There was no significant reduction in AF recurrence between the groups. A meta-analysis of 4 trials including the ones described earlier, analyzing 424 patients, demonstrated no benefit for statins in preventing AF recurrence.…”
Section: Medications For Maintenance Of Srmentioning
confidence: 83%
“…100 In the statin therapy for the prevention of atrial fibrillation trial, 64 patients were randomized to atorvastatin or placebo starting 1 week before cardioversion, then continued for 12 months. 101 There was no significant reduction in AF recurrence between the groups. A meta-analysis of 4 trials including the ones described earlier, analyzing 424 patients, demonstrated no benefit for statins in preventing AF recurrence.…”
Section: Medications For Maintenance Of Srmentioning
confidence: 83%
“…33 However, as shown in Figure 7, Rac1 activity was not increased in RA samples from patients with persistent AF, and atorvastatin did not cause a mevalonate-reversible reduction in superoxide production in this group, in agreement with studies indicating little or no beneficial effect of statins in the secondary prevention of AF or in disease states (eg, heart failure) associated with atrial structural remodeling. [12][13][14][15] It should be noted that our studies in human atrial tissue are limited to samples of the RA appendage. Although the similarities in the findings obtained in human and goat RA myocardium in the presence of longstanding AF suggest that the goat is a representative model of human AF, we cannot be certain that the human LA myocardium would show the same results.…”
Section: Reactive Oxygen Species and Atrial Fibrillation-induced Elecmentioning
confidence: 99%
“…[7][8][9] In humans, NOX2-containing NADPH oxidases are the main source of ROS production in both right atrial (RA) homogenates and isolated myocytes, 6 and RA NADPH-stimulated superoxide production is independently associated with an increased risk of developing AF after cardiac surgery. 10 Statins prevent AF-induced early electric remodeling in dogs 9 and reduce the occurrence of postoperative AF in patients undergoing cardiac surgery 11 but are less effective in the secondary prevention of AF [12][13][14] or in the presence of significant atrial structural remodeling (eg, in heart failure 15 ). By inhibiting HMG CoA reductase, statins prevent the isoprenylation of Rac1 and reduce ROS formation by NADPH oxidases in cardiac tissue.…”
mentioning
confidence: 99%
“…This suggestion could explain why statins, which inhibit NOX2 activation, are effective in AF primary prevention and less effective in secondary prevention, where other sources of reactive oxygen species are associated with AF. 32 The use of markers of antioxidant status or oxidative stress may also help in identifying patients at high risk of AF recurrence. Finally, vitamin E supplementation could represent an interesting therapeutic option that should be considered in future trials in patients with persistent AF undergoing cardioversion.…”
Section: Discussionmentioning
confidence: 99%